2020
DOI: 10.1371/journal.pmed.1003256
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed food intake in association with BMI change and risk of overweight and obesity: A prospective analysis of the French NutriNet-Santé cohort

Abstract: Background Ultra-processed food (UPF) consumption has increased drastically worldwide and already represents 50%-60% of total daily energy intake in several high-income countries. In the meantime, the prevalence of overweight and obesity has risen continuously during the last century. The objective of this study was to investigate the associations between UPF consumption and the risk of overweight and obesity, as well as change in body mass index (BMI), in a large French cohort. Methods and findings A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
167
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(195 citation statements)
references
References 75 publications
18
167
0
10
Order By: Relevance
“…In this study, the association between UPF and depressive symptoms is more significant among inactive people, which may be mediated by obesity. Previous literature has described a positive association between UPF and obesity (25,47,48).…”
Section: Discussionmentioning
confidence: 91%
“…In this study, the association between UPF and depressive symptoms is more significant among inactive people, which may be mediated by obesity. Previous literature has described a positive association between UPF and obesity (25,47,48).…”
Section: Discussionmentioning
confidence: 91%
“…Considering mounting scientific literature linking UPF to adverse health outcomes [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], an increasing number of countries have started to implement public policies to limit their consumption. Approaches such as taxes, restricting where these products can be sold, and advertisement regulations have been utilized in some countries [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between food processing and diet quality and health of the French population has been evaluated through a series of studies that used the NOVA (non-acronym name) classification and data from the NutriNet-Santé cohort [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. According to NOVA, ultra-processed foods (UPFs) are the formulation of food substances involving processes and ingredients exclusively employed in industrial production [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several nationally representative cross-sectional studies have shown a significant association between consumption of ultra-processed foods and higher body mass index (BMI) or waist circumference (WC) and the prevalence of obesity in Australia [ 21 ], Brazil [ 22 ], Canada [ 23 ], the USA [ 24 ], and the UK [ 25 ]. In addition, in prospective cohort studies conducted in France [ 26 ], Spain [ 27 ], and the UK [ 28 ], participants with higher consumption of ultra-processed foods presented a higher BMI or higher risk of being overweight or obese than those with lower consumption. Recently, a randomized controlled study conducted in the USA showed that higher consumption of ultra-processed foods caused increased energy intake and body weight gain [ 29 ].…”
Section: Introductionmentioning
confidence: 99%